Pseudomonas aeruginosa bloodstream infection in patients with hematological diseases: Clinical outcomes and prediction model of multidrug-resistant infections. Issue 1 (January 2023) - Zhao, Yuanqi; Lin, Qingsong; Zhang, Tingting; Zhen, Sisi; Wang, Jieru; Jiang, Erlie; Mi, Yingchang; Qiu, Lugui; Han, Mingzhe; Wang, Jianxiang; Feng, Sizhou
Highlights: Long-term antibiotic use linked to multidrug-resistant infections. Bloodstream infection prognosis is closely related to time to effective treatment. The use of antibiotic prophylaxis in patients with neutropenia need to be weighed. There are still many drugs with in vitro activity against CR P. aeruginosa .